KEDINAMIKAN SYARIAH DALAM MEMENUHI TUNTUTAN MU'AMALAH PERBANKAN MODEN - Bakar, Mohd Daud (Jurnal Syariah, 2019)
The Shari 'ah was revealed to govern the acts of man. As man and society change, Islamic law ought to deal with new developments adequately. Undoubtedly, the field of commercial transactions have encountered the most rapid changes and developments in Muslim society to which Islamic law has to address. Issues such as freedom of contract and nominate contracts are amongst the issues which constitute the tool for a revitalisation of Islamic mu 'amalah in modern banking and finance. Equally important is the legal framework that will safeguard the prospects of Islamic commercial law without which the future of Islamic mu 'amalah will be declined and diminished.